The Educational Thought Of KH. Imam Zarkasyi In Contemporary Islamic Education - Bintang Arif Samudra; Wahyudin Nur Nasution; Sholihah Titin Sumanti (AFKARINA: Jurnal Pendidikan Agama Islam, 2026)
Contemporary Islamic education faces critical challenges, including the dichotomy of knowledge, moral degradation, and the weakening of educational authority amid unfiltered globalization. This study aims to analyze the educational thought of K.H. Imam Zarkasyi as an alternative solution and to formulate an integrative conceptual model for contemporary Islamic education. Specifically, it examines curriculum conceptualization, teaching methods, and the repositioning of educators’ roles. The research is situated within Islamic educational thought, particularly pesantren-based education, focusing on the Kulliyatul Mu’allimin al-Islamiyah (KMI) system. It employs a qualitative approach using a library research model, drawing on primary and secondary sources. Data are collected through documentation and analyzed descriptively to construct a systematic understanding. The findings reveal that Imam Zarkasyi developed an integrative curriculum based on the principle of “100% religious and 100% general knowledge,” effectively eliminating the dichotomy of science. His pedagogical approach emphasizes holistic learning through exemplary conduct (uswah hasanah) and a continuous educational environment (bi’ah tarbawiyah). Moreover, educators are repositioned not merely as instructors, but as mu’allim, murabbi, and mu’addib grounded in the values of the Panca Jiwa. These findings underline the relevance of his thought in addressing contemporary educational challenges and fostering intellectually and morally grounded Muslim generations.